The Role of Parent-child Relationship in Parental Financial Teaching and Financial Behaviour of Students - Xolile Antoni (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: The parent-child relationship plays a crucial role in facilitating financial socialisation and has been found to influence students' financial behaviour. Research on this topic, however, remains scarce despite the prevalence of poor financial literacy and risky financial behaviour among students in the Eastern Cape, South Africa. This study limited parental financial socialisation practices to financial teaching. Purpose: This study will investigate the role of parent-child relationship on parental financial teaching and financial behaviour. Methods: The study adopted a quantitative research design, and primary data was collected from 360 students at Eastern Cape University using a closed-end questionnaire. In addition, correlation and multiple regression analyses were used to test the study's hypothesis. Findings: The results show that the parent-child relationship significantly influences parental financial teaching and financial behaviour. Furthermore, parental financial teaching mediates the role of the parent-child relationship on financial behaviour. The results show that students who have a close relationship with parents in which parents show love and acceptance are more receptive to parental teaching on financial matters and thus, in turn, parental financial teaching influences students' financial behaviour. Conclusion: Therefore, the quality of parent-child relationships is an important factor influencing the success of parental financial socialisation, which, in turn, improves students' financial outcomes. Research implication: The implication for financial education is that parents should be involved in financial education programmes and tasked with the responsibility of guiding their children's financial behaviour. This study makes valuable contributions